Development of processed cheese with aqueous extract of Moringa oleifera seed (Research, Society and Development, 2021)
In this study, processed cheese was produced with a total and partial substitution of xanthan gum by Moringa seed extract and stored at 4ºC. Chemical composition pH, acidity, color, texture, and rheology were studied. The chemical composition differed significantly (p